The impact of interventions delivered through farmer producer organizations on agricultural and empowerment outcomes in India - Ray, Soumyajit; Raghunathan, Kalyani (International Food Policy Research Institute, 2023)
In India, farmer producer organizations (FPOs) promote collective action among small and marginalized farmers, especially women. By facilitating resource pooling and coordination of production activities, improving market access, and providing training and extension, FPOs can contribute to higher agricultural incomes for smallholder farmers. Women’s FPOs also help formalize women’s roles in agriculture, offer them remunerative employment, and enhance their engagement across the value chain. We use two rounds of panel data on 1,200 households in the eastern Indian state of Jharkhand to assess the impact of women-only FPOs. The FPO interventions we evaluate are threefold: strengthening collectives, coordinating and improving agricultural practices, and providing gender-based training. Women FPO members in the treatment arm received these interventions; those in the control arm did not. We match treatment and control blocks based on economic and developmental characteristics from secondary data sources, and then match individuals using baseline survey characteristics. We estimate impacts using difference-in-difference models with nearest neighbour matching techniques—with household assets, agricultural yields and profits, and women’s empowerment as our primary and secondary outcomes. We find some impact of FPO interventions on agricultural outcomes, but mixed evidence of their impact on women’s empowerment. This research contributes to the existing body of literature by rigorously assessing the impact of FPOs on agriculture-related and women’s empowerment–related outcomes. The findings will provide policymakers and practitioners with insights into designing strategies to promote sustainable agricultural growth and gender equity